“A smooth transition or a giant leap?” The challenges posed by the transition from secondary education to higher education in relation to EMI in Sri Lanka - Mahawattha , Nadee; Rassool, Romola (Studies in Second Language Learning and Teaching, 2023)
Although bilingual education has been offered in some schools of Sri Lanka since 2001, primary and secondary school education has been conducted mainly in the first language (L1), that is, Sinhala/Tamil. As a result, most students sit for the General Certificate of Education – Advanced Level (GCE (A/L) examination, which determines university entry, in their L1. Thus, the majority of students entering state universities do so after receiving their entire education in their L1. At the tertiary level, where many (if not most) degree programs are conducted in the English medium, students struggle to make the transition from Sinhala/Tamil medium instruction to English medium instruction (EMI). This study examines the challenges faced by students and lecturers in three selected state universities due to this language transition. It employs a qualitative research design. Data were collected through official documents and semi-structured interviews with forty academics. Three focus group interviews were conducted with thirty undergraduates. In addition, eighteen non-participant lectures were observed in mainstream classrooms. The findings indicate several structural, institutional, and linguistic challenges on the way to a successful implementation of EMI in state universities and demonstrate that the transition from GCE (A/L) to EMI in universities is a challenging experience for both students and lecturers. We propose that the concept of academic literacies be used as a productive means of supporting undergraduates through their transition to EMI.